Characteristics and Limits of a National Initiative of Integrity and Anti-corruption for Local Governments of Brazil - Silva, Rodrigo S. De Bona da (Revista del CLAD Reforma y Democracia, 2021)
This article analyzes the characteristics and limits of an integrity and anti-corruption policy of the Brazilian federal government offered to local governments. The Time Brazil Program is an initiative of the Office of Comptroller General of the Union (CGU) created in 2019, based on local policies implemented since its creation in 2003. After content analysis, it can be characterized, at the micro level, as a top-down strategy without enforcement of voluntary adhesion and dependent on the mayor, in which compliance-based internal actions predominate. Adherent, to a large extent, to international recommendations, it proposes incremental advances with emphasis on internal controls for the prevention and detection of administrative corruption, mainly petty corruption. It assumes that the irregularities are caused by lack of knowledge and regulation, and proposes the creation of filters and sanctions to increase control and reduce rent-seeking. On the other hand, there are limits that may affect its implementation and effectiveness, mainly in small cities, such as: lack of measures to act on grand corruption and politics; lack of value-based and ethic-based strategies to stimulate changes in organizational culture; emphasis on local regulation of good practices (soft law), but only internally, without interaction with the legislative power, which is fragile to changes of governments. Also, there is no forecast of indicators of long-term results and impact, beyond the regulatory adherence. The analysis characterizes Time as a complex policy and strongly subject to implementation gaps, as it contains limitations from its design. Its success depends on the construction of a local anti-corruption agenda and on the capacity of the comptroller’s office which in turn depends on the approval of laws by the legislature, in addition to pressure from local society and the horizontal accountability system. The development of local leadership capacity and effective partnerships within intergovernmental coalitions are factors that, if included, could facilitate proper policy implementation. Future research can assess their impacts and effectiveness.